Cultural Integration in Islamic Religious Education Material at SMPN 6 Bolano Lambunu - Hikmawati; Asman Deeteng; Nasrul (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2026)
Islamic Religious Education (PAI) serves as a vital foundation for shaping students’ moral and spiritual character within Indonesia’s culturally diverse society. This study examines how the integration of local cultural values into PAI instruction can enhance the contextualization and internalization of Islamic teachings among students at SMPN 6 Bolano Lambunu, Parigi Moutong Regency, Central Sulawesi. Using a qualitative descriptive approach, data were collected through classroom observations, in-depth interviews with PAI teachers, principals, students, and community leaders, as well as documentation of religious and cultural activities. The findings reveal that integrating local cultural practices such as gotong royong (mutual cooperation), respect for elders, and community celebrations like the Prophet’s Birthday creates a meaningful bridge between Islamic values and students’ daily social realities. This integration fosters students’ religious awareness, tolerance, and moral responsibility while reinforcing cultural identity and pride. The results also demonstrate that inclusive and multicultural PAI learning, which accommodates religious diversity and promotes interfaith respect, contributes significantly to building harmonious and empathetic social relations in the school environment. Furthermore, teachers’ exemplary behavior plays a crucial role as both facilitators and moral role models in ensuring that Islamic values are internalized holistically cognitively, affectively, and behaviorally. Overall, this study highlights the effectiveness of a culturally integrative and multicultural approach in developing character education through Islamic Religious Education, offering a replicable model for schools in other culturally diverse regions